2016
DOI: 10.4081/monaldi.2009.334
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive changes after Carotid Endarterectomy

Abstract: The aim of this study was to investigate changes in cognitive function following carotid endarterectomy (CEA). In 74 asymptomatic CEA patients cognitive function, depression, laterality and severity of stenosis, cerebral Computer Tomography results, and ischemic heart diseases were measured preoperatively. The sample included 31 patients with dementia and 43 patients without any symptom of dementia. Cognitive function was measured again at 3 months postoperatively using a brief standardised test. After control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, asymptomatic patients with stenosis greater than 75% experienced an improvement in cognitive function after CEA. Cognitive function increased significantly between the preoperative measurement and at 3 months following CEA in patients with and without dementia [ 33 ].…”
Section: Endarterectomy Improves Qolmentioning
confidence: 99%
“…In addition, asymptomatic patients with stenosis greater than 75% experienced an improvement in cognitive function after CEA. Cognitive function increased significantly between the preoperative measurement and at 3 months following CEA in patients with and without dementia [ 33 ].…”
Section: Endarterectomy Improves Qolmentioning
confidence: 99%
“…Patients can demonstrate cognitive changes after CEA due to the common due to the common fluctuations in CBF during and after surgery; approximately 20%–25% demonstrate cognitive dysfunction 18,23 and approximately 10%–15% demonstrate cognitive improvement, 1,2,9,11,12,39 while approximately 60%–70% demonstrate no cognitive changes. 14,40 Current unpublished data suggest that patients with reduced CBF velocity during cross-clamping of the carotid artery are more likely to exhibit cognitive dysfunction 1 day after CEA.…”
mentioning
confidence: 99%
“…Numerous studies have shown that living with a chronic disease affects the person's mental health. For example, in cerebrovascular diseases, there is permanent damage to the brain tissue caused by a somatic disorder; coronary heart disease affects the severity of depressive symptoms in surviving apoplexy [6], and the removal of the vascular pathology substrate often leads to improved cognitive function and reduced depression [7]; depression often develops as part of type-2 DM and has been identified as one of the factors that accelerates the onset of advanced degenerative changes to small blood vessels. Patients on hemodialysis face a number of difficulties brought on by the nature of the disease.…”
Section: Introductionmentioning
confidence: 99%